2022
DOI: 10.3390/genes13112140
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Sequencing Reveals Tgf-β-Mediated Noncoding RNA Regulatory Mechanisms Involved in DNA Damage in the 661W Photoreceptor Cell Line

Abstract: Transforming growth factor β (Tgf-β), a pleiotropic cytokine, can enhance DNA repair in various cells, including cancer cells and neurons. The noncoding regulatory system plays an important role in Tgf-β-mediated biological activities, whereas few studies have explored its role in DNA damage and repair. In this study, we suggested that Tgf-β improved while its inhibitor LSKL impaired DNA repair and cell viability in UV-irradiated 661W cells. Moreover, RNA-seq was carried out, and a total of 106 differentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Finally, we combined hub genes and related miRNAs and lncRNAs to reconstruct the ceRNA network and performed RT-qPCR validation for these genes. Based on previous studies, the effect of most ceRNA networks was identified in ophthalmic physiopathological processes, suggesting our result might help understand the mechanism of primary and secondary photoreceptor degenerations (Chen et al, 2021;Huang Y. et al, 2022;Wang N. et al, 2022). However, there were several limitations in this study.…”
Section: Discussionmentioning
confidence: 85%
“…Finally, we combined hub genes and related miRNAs and lncRNAs to reconstruct the ceRNA network and performed RT-qPCR validation for these genes. Based on previous studies, the effect of most ceRNA networks was identified in ophthalmic physiopathological processes, suggesting our result might help understand the mechanism of primary and secondary photoreceptor degenerations (Chen et al, 2021;Huang Y. et al, 2022;Wang N. et al, 2022). However, there were several limitations in this study.…”
Section: Discussionmentioning
confidence: 85%